Optimalisasi Pemanfaatan Lahan dan Sumber Air melalui Kombinasi Budidaya Dalam Ember dan Akuaponik untuk Peningkatan Gizi Masyarakat Desa Serayu Larangan, Kabupaten Purbalingga - Emyliana Listyowati; Anjaini, Jefri; Hamdan Syakuri; Anandita Ekasanti; Dewi Nugrayani; Tohap Simangunsong; Nurchamidah; Widhiatmoko Herry Purnomo (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Budikdamber (fish farming in buckets) and aquaponics are integrated farming technologies that integrate catfish with kale and mustard greens. catfish with kale and mustard greens. This system is implemented in Serayu Larangan Village, Purbalingga Regency, as an effort to improve food security and sustainable land utilization. and sustainable land utilization. The implementation of this program showed positive results, with optimal catfish growth and productive kale and mustard greens harvests. kale and mustard greens are productive in a short time. This integration utilizes fish organic waste as nutrients for plants, thus creating a mutually supportive ecosystem. creating a mutually supportive ecosystem. The success of this program opens up potential for the development of Budikdamber and aquaponics as a business opportunity for the Serayu Larangan Village community. In addition to supporting household food security household food security, this system offers an economical and environmentally friendly business alternative. environment. Based on the results of the implementation, the Budikdamber and aquaponics program can be concluded as a successful and innovative step. program can be concluded as a successful innovative step that can be adapted to other areas with similar conditions. adapted for other areas with similar conditions. This program is an example of application of integrated cultivation technology that is efficient and sustainable